Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan KFC Artha Gading - Pramesti, Rizki Ayu; Sambul, Sofia A. P.; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine the effect of Reward and Punishment on the Employee Performance of KFC Artha Gading North Jakarta. Reward is a form of appreciation to a certain achievement given, both by and from individuals or an institution which is usually given in the form of material or speech. Punishment is a way to direct a behaviour in accordance with the behaviour that applies in general. Performance is the result or level of success of a person as a whole during a certain period in carrying out tasks compared to various possibilities, such as standard results of work, targets or targets or criteria that have been determined in advance and have been agreed upon. This study uses a quantitative approach, with a sample of 32 respondents who are employees of KFC Artha Gading North Jakarta. Research results show that : reward has a positive and significant effect on the performance of employees of Artha Gading Jakarta, punishment has a positive and significant effect on the performance of employees of Artha Gading Jakarta, reward and positive and significant effect on the performance of employees of Artha Gading Jakarta. Punishment has a positive and significant effect on the performance of employees of Artha Gading Jakarta.